Kenyan diets: Quality, affordability, and preferences - Ecker, Olivier; Comstock, Andrew R.; Pauw, Karl (International Food Policy Research Institute, 2023)
Dysfunctions in food systems in developing countries prevent many people from consuming a healthy diet (FAO et al. 2021), and Kenya is no exception. Globally, poor-quality diets are the leading cause of all forms of malnutrition (Afshin et al. 2019; Willet et al. 2019). In Kenya in 2020, an estimated 19 percent of children under five years of age were stunted (UNICEF, WHO, and World Bank 2021); in 2014, 33 percent of women aged 15–49 years were overweight or obese (KNBS et al. 2015), while recent regional trends in adults’ body mass index suggest a rapid increase in the prevalence of overweight and obesity (Abarca-Gomez et al. 2017). The number of deaths resulting from noncommunicable diseases (NCDs), such as coronary disease, type 2 diabetes, and cancer, is projected to surpass malaria and tuberculosis by 2030 (Mkuu et al. 2021). Malnutrition and NCDs can have lifelong health consequences and high social and economic costs for individuals and societies alike, including from impaired human capital formation, reduced labor productivity, and high healthcare costs (Popkin et al. 2006; Shekar, Heaver, and Lee 2006; Victora et al. 2008; Black et al. 2013).